Pengaruh Keluarga, Tokoh Agama dan Teman terhadap Perilaku Memilih Pemilih Pemula - Meike Kurniawati (Fakultas Psikologi Universitas Pancasila, 2023)
In the Indonesian General Election, 14 February 2024, it is predicted that first-time voters will increase significantly compared to the previous election. New voters are usually the focus of attention of parties or contestants because of their large number, and new voters are determinants the future, because most of them are the younger generation (millennial and Z). They usually do not have sufficient political education, and also have not made their choice. In political marketing, if someone doesn't have a choice, they usually tends to seek information, one of which is from a reference group. Reference groups are groups that become a reference for someone in behaving. Reference groups can consist of family (Parents), Religious Leaders and Peers. The purpose of this study was to determine the influence of Parents, Religious Leaders and Friends on the voting behavior of novice voters. Quantative research, data obtained from 278 respondents, analysis using simple regression. The results showed that Parents had a significant influence on the voting behavior 1.2%, Religious Leaders 7.1% and the influence of Friends 7.9%.